Synchronic and diachronic aspects of valency-reducing devices in Oceanic languages - Janic, Katarzyna (Lingua Posnaniensis, 2016)
This paper sketches out valency-reducing devices available in Oceanic languages. The Proto-Oceanic prefix *paRi- and suffix *-akin[i] are specifically the focus of the discussion, being approached from both synchronic and diachronic perspectives. I explain the currently attested functions performed by the reflexes of these two morphemes by assuming that the evolution went in a particular direction: from a very general function to a more specialized, concrete one. Among different functions performed by the reflexes of *paRi- and *-akin[i] within the valency-reducing domain, I will show that the antipassive has not been fully recognized and properly designated in linguistic descriptions of the Oceanic languages yet.